Resolution Of Sharia Economic Disputes In Class 1 A Religious Court In Makassar - Nurhaedah, Nurhaedah; Asriati, Asriati (Al-'Adl, 2024)
The research aims to analyze the effectiveness of the dispute resolution mechanism, identify the challenges faced, and evaluate its impact on the development of Islamic economics. The method used in this research is a qualitative approach that includes court decisions related to sharia economic disputes. The results of this study indicate that the development and comprehensive approach in handling economic disputes is very important, especially in sharia economic law approaches. However, sharia economic dispute cases have high complexity and caution in determining economic decisions, because the approaches have significant differences to economic dispute cases in general. The findings are expected to serve as a foundation for the development of more effective policies and practices in handling sharia economic disputes in the future. So that the resolution of economic disputes the ability of the judiciary to provide decisions objectively.